A study of grid artifacts formation and elimination in computed radiographic images. - Lin CY; Lee WJ; Chen SJ; Tsai CH; Lee JH; Chang CH; Ching YT (Journal of Digital Imaging, 2006)
Computed radiography (CR) has many advantages such as filmless operations, efficiency, and convenience. Furthermore, it is easier to integrate with the picture archiving and communication systems. Another important advantage is that CR images generally have a wider dynamic range than conventional screen film. Unfortunately, grid artifacts and moiré pattern artifacts may be present in CR images. These artifacts become a more serious problem when viewing CR images on a computer monitor when a clinic grade monitor is not available. Images produced using a grid with higher frequency or a Potter-Bucky grid (i.e., a moving grid, Bucky for short) can reduce occurrence but cannot guarantee elimination of these artifacts [CR & PACS (2000); Detrick F (2001), pp 7-8]. In this paper, the formation of the artifacts is studied. We show that the grid artifacts occur in a narrow band of frequency in the frequency domain. The frequency can be determined, accurately located, and thus removed from the frequency domain. When comparing the results obtained from the proposed method against the results obtained using previous computer methods, we show that our method can achieve better image quality.